About saints and superheroes: A test of Paulhus’ model of social desirability (2002) - Galić, Zvonimir; Jerneić, Željko; Parmač Kovačić, Maja (2008)
The aim of this study was to test Paulhus' model which states that there are two social desirability factors (egoistic and moralistic bias), both of which have conscious and unconscious aspects (management and enhancement). In our study participants completed the Comprehensive Inventory of Desirable Responding (Paulhus, 2006) in three situations: honest (N=224), “ fake good-agency” (N=249) and “ fake good-communion” (N=196). As expected, egoistic bias increased most in “ fake good– agency” , and moralistic bias in “ fake good– communion” situation. However, the increase was present on enhancement as well as on management scales. Thus, the new model was only partially confirmed.
29th International Congress of Psychology (20.07.-25.07.2008. ; Berlin, Njemačka)
Projekt MZOS
ENG